17 The role of american college of physicians clinical guidelines on improving healthcare value and reducing harms of overdiagnosis and overtreatment: example from breast and colorectal cancer screening. (4th December 2019) - Wilt, Timothy; Qaseem, Amir
Abstract : Purpose: Describe the structure, methods, and products of the American College of Physicians Clinical Guideline Committee (ACP-CGC) and the role their guidelines and guidance statements have in enhancing high value care including evaluating, describing, and reducing harms of overdiagnosis and overtreatment. We highlight work regarding breast and colorectal cancer (CRC) screening; two situations where commercial and media factors drive overdiagnosis. Methods: The ACP has been developing guidelines since 1980. ACP's guideline development program has evolved with advancements in the field. Enhancements to its policies and methods include more stringent disclosure of interests and management of conflicts, public involvement, the use of the Grading of Recommendations Assessment, Development and Evaluation (GRADE) methods, and reporting formats that consider overall value of care taking into considerations variables such as patient comorbidities, patient values and preferences, and costs. In addition to clinical members, the ACP-CGC includes non-physician public members and a Public Panel to develop key questions, interventions, rank outcomes including magnitude and impact of overdiagnosis and overtreatment, and assess evidence certainty. ACP-CGC develops guidance statements on topics to reconcile conflicting guidelines and help clinicians provide evidence-based healthcare. ACP-CGC accomplishes this by rigorously reviewing available guidelines and their evidence base, and developing guidance based on an assessment of the reported benefits, harms, costs, and patient preferences and values. Results: ACP-CGC guidance statements on breast and CRC screening in average risk adults were derived from appraisal of selected published guidelines and their available evidence. We developed screening guidance according to age (sex for CRC), life expectancy, and screening modality. We describe the reported association between mammography screening and overdiagnosis and overtreatment by age, highlight overdiagnosis and overtreatment as an important harm of more intensive screening strategies, and emphasize how implementation of ACP-CGC guidance statements can improve health in part through reducing overdiagnosis. For CRC screening we found no data on overdiagnosis and overtreatment. However, based on the known natural history of CRC and CRC precursors, overdiagnosis is likely substantial. For both breast and CRC screening we note that guidance statements are derived from evidence about screening benefits and harms across populations and screening modalities and include overdiagnosis in determining net benefit. We highlight how our guidance statements that encourage less intensive screening strategies including starting screening at a later age, stopping screening in those with limited life expectancy due to advanced age or comorbidities, widening screening intervals, and using less sensitive screening tests improve healthcare value by maintaining clinical benefits while reducing harms and costs including overdiagnosis. Conclusion: ACP-CGC aims to enhance healthcare value through development and dissemination of evidence-based guidelines and guidance statements. Our breast and CRC screening guidance statements improve healthcare delivery and counter some of the commercial and media drivers of overly intensive screening that lead to overdiagnosis. ACP-CGC provides the public, healthcare providers, and healthcare systems with rigorous, readable, reliable, and relevant information on benefits and harms including the clinical impact of overdiagnosis and overtreatment and develops practice suggestions to reduce their harms.